Attention direction in static and animated diagrams - Lowe, Ric; Boucheix, J. (Springer, 2010)
Two key requirements for comprehending a diagram are to parse it into appropriate components and to establish relevant relationships between those components. These requirements can be particularly demanding when the diagram is complex and the viewers are novices in the depicted domain. Lack of domain-specific knowledge for top-down guidance of visual attention prejudices novices’ extraction of task-relevant information. Static diagrams designed for novices often include visual cues intended to improve such information extraction. However, because current approaches to cueing tend to be largely intuitive, their effectiveness can be questionable. Further, animated diagrams with their perceptually compelling dynamic properties pose new challenges for providing appropriate guidance of attention. Using a hydraulic circuit diagram example, this paper considers human information processing influences on the direction of visual attention in complex static and dynamic diagrams. It aims to stimulate a more principled approach to cue design.